Development of an online psychological intervention to prevent depression in patients with atrial fibrillation: lessons learned in a user-centered design study - Charlotte Helmark; Robert Ahm; Axel Brandes; Søren J. Skovbakke; Jens Cosedis Nielsen; Lisbeth Frostholm; Rod S. Taylor; Susanne S. Pedersen (Pilot and Feasibility Studies)
Abstract Background Approximately 30% of patients with atrial fibrillation suffer from depression. Depression in patients with atrial fibrillation is associated with poor health outcomes, reduced health-related quality of life, and elevated societal costs. Preventing depression in this population may therefore lead to better health outcomes for the individual patient and reduced burden on society. Online psychological interventions are innovative and evidence-based modes of healthcare delivery. The objective was—through a user-centered design—to develop a personalized online psychological intervention aiming at preventing depression in patients with atrial fibrillation. Methods Guided by the Intervention Mapping framework for the development of complex interventions, we used a qualitative design and conducted a series of collaborative workshops with patients (n = 8) with atrial fibrillation. Results Through intensive collaboration, we developed the HOPE-AF intervention targeting nine risk factors for depression that were meaningful to patients. It contains four basic modules that give effective tools to handle daily psychological struggles. Furthermore, patients will receive personal risk factors modules. The evidence-based psychological methodology was applied to all modules. Primary lessons learned were (1) engaging patients from the start to ensure the intervention becomes meaningful; (2) using positive phrasing in all patient-related materials to promote motivation; (3) incorporating patients’ choice of preference where possible to personalize the intervention. Conclusion Based on a user-centered design, the HOPE-AF intervention aiming to prevent depression in patients with AF, was developed. It was confirmed that it is crucial to engage end-users in the development of complex interventions to accommodate their needs and preferences. The Hope-AF intervention will now be tested in a feasibility study.